Genetic polymorphism and phylogenetic analysis of 15 autosomal STR markers in the Santal indigenous population of Bangladesh: Genetic polymorphism and phylogenetic analysis - Hasan, Md Mahamud; Rahman, Md Hadisur; Akhteruzzaman, Sharif (Bioresearch Communications, 2021)
Fifteen autosomal STR markers, namely D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D19S433, vWA, TPOX, D18S51, D5S818, and FGA were typed using AmpFlSTR® Identifiler® Plus PCR amplification systems in 132 unrelated Santal individuals of Bangladesh. Forensic efficiency parameters like, matching probability (MP), power of discrimination (PD), polymorphism information content (PIC), power of exclusion (PE), typical paternity index (TPI), observed heterozygosity (Hobs), and expected heterozygosity (Hexp) were calculated for all the loci. No deviations from Hardy-Weinberg equilibrium were detected for the loci after Bonferroni correction. The combined matching probability (MP), combined power of discrimination (PD) and combined power of exclusion (PE) for the 15 tested STR markers were 8.38 x 10-17, 0.999999998 and 0.0.999993866, respectively. A comparison of the locus wise allele frequencies of autosomal STR data of the Santal population with the published geographically close population data based on Nei’s genetic distance revealed that the Santal population is closely related to Munda population from Jharkhand, India. Bioresearch Commu. 7(2): 1004-1009, 2021 (June)